Molecular Identification and Characterization of Seeded Turf Bermudagrass Cultivars Using Simple Sequence Repeat Markers. (1st November 2018) - Yang, Lie; Wu, Yanqi; Moss, Justin Q.; Zhong, Sheng; Yang, Bin
Abstract : Core Ideas: Six to nine signature alleles were revealed for each of the four standard seeded bermudagrass cultivars with 32 SSR markers. All individual bermudagrass plants were correctly assigned to their source cultivars using the SSR markers. The SSR marker profiles can be effectively used to identify blinded individuals to the source cultivars. Common bermudagrass [ Cynodon dactylon (L.) Pers. var. dactylon ], is increasingly used in the development of seed‐propagated turf cultivars. Each seeded bermudagrass cultivar is a heterogeneous population composed of heterozygous genotypes. Therefore, the accurate identification of seeded bermudagrass cultivars is a challenge and has not yet been reported although this kind of information would be valuable for new cultivar development, seed certification, and intellectual property protection. Accordingly, the objectives of this study were (i) to characterize the genetic diversity within and relatedness between turf‐type seeded cultivars; and (ii) to investigate the assignment of individuals to their source cultivars using simple sequence repeat (SSR) markers. Four seeded cultivars, NuMex Sahara, Princess‐77, Riviera, and Yukon were used in the investigation. Thirty individual plants, two bulk samples, and two additional individual plants from each of the four cultivars were genotyped with 32 SSR markers that were sampled to span a major portion of the species genome. The number of alleles amplified per SSR locus ranged from 3 to 10, with a mean of 5. Six to nine signature alleles were identified for each of the four cultivars. Genetic distance estimates and clustering results were consistent with the respective breeding history. Individual plants formed four distinct groupings corresponding exactly to the four cultivars and all individuals were correctly assigned to their respective source cultivars. The total gene diversity of the four cultivars was 0.257, indicating high diversity. The posterior test also indicated that bulk samples and two additional individual plants were clearly assigned to their source cultivars. The approach developed in this study is useful for the accurate identification of seeded bermudagrass cultivars.